“Caracterización de mujeres con riesgo de alteración de la diada materno-fetal por ruptura prematura de membranas, noviembre 2017-febrero 2018.” - Barrionuevo Mendoza, Samanta Katherine (2018)
The present study has an objective to determine the socio-demographic, clinical, obstetric and risk factors related to diagnosis of Nursing: risk of alteration of the dyad maternal-fetal in women with Premature Rupture of Membranes of Hospital Provincial General Docente de Riobamba, it was conducted a descriptive study of cross-section and quantitative character. A non-probabilistic sample was chosen of pregnant women with Premature Rupture of Membranes they entered the Gynecology and Obstetrics service in a period of 45 days, getting 17 women participants. An interview guide was applied for the collection of data related to the diagnosis of Nursing, subsequently the information was analyzed obtaining as a result: Socio-demographic factors among the most relevant were the adulthood, followed by the level of secondary education, low socio-economic level, standing time more than 6 hours, the consumption of toxic substances was not recorded. Among the most relevant clinical factors urinary tract and cervicovaginal infections predominated, less frequently the intercourse, there were no cases of patients with previous pathologies, neither self-medication. The most predominant obstetric factors were gestational age affecting more frequently in the third trimester of pregnancy, scarce obstetric controls and oligohydramnios as a consequence of Premature Rupture of Membranes. In risk factors related to diagnosis the most relevant was complications of pregnancy, inadequate prenatal cares, the therapeutic regimen and fetal oxygen commitment it was presented in a third of the population.